Supuestos, distancias y apropiación de la tecnología en la atención institucional de la salud - Lemus Alcántara, Sergio (2024)
Health care is an institutionalized activity under the control of the State. Current public policy offers benefits limited to scientific progress and the use of technology for its potential to solve highly complex problems. However, in public hospitals, the distance between the discourse and the concretion of care is observed, whose epitome is human praxis. This work is the result of a research project of the Master’s and Doctoral Program in Medical, Dental and Health Sciences of the National Autonomous University of Mexico (UNAM). Uses the ethnographic method in the clinical context. Findings open the discussion on the scope and implications of how technology is used in the clinical context. Currently, the use of technology is a topic of research in the Department of History and Philosophy of Medicine of the UNAM, coordinated by Professor Alfredo Paulo Maya.